2003
DOI: 10.1097/01.inf.0000078163.80807.88
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neonatal sepsis in developing countries

Abstract: Physical signs can be used to identify young infants at risk of severe disease, however with limited specificity, resulting in large numbers of unnecessary referrals. Further studies are required to validate and refine the prediction of severe disease, especially in the first week of life, but there appear to be limits on the accuracy of prediction that is achievable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1
5

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 14 publications
5
104
1
5
Order By: Relevance
“…This observation is in accordance with reports from two other developing countries 8 . Similarly in a study conducted by Martin M Meremikwu et al in Nigeria, they found that Staphylococcus aureus was isolated in 48.7% and E coli in 23.4% as the most frequent isolates 4 .…”
Section: Discussionsupporting
confidence: 83%
“…This observation is in accordance with reports from two other developing countries 8 . Similarly in a study conducted by Martin M Meremikwu et al in Nigeria, they found that Staphylococcus aureus was isolated in 48.7% and E coli in 23.4% as the most frequent isolates 4 .…”
Section: Discussionsupporting
confidence: 83%
“…The age at presentation of LONNS in our study was day 8 in scalp shaved group and day 6 in no scalp shaved group, which was different from Weber et al 12 (10 th day),and mean weight(2818 gms) was less than…”
Section: Discussioncontrasting
confidence: 48%
“…Weber et al 12 (3121 gms) but reflecting our natonal average of 2800 gms. 8 There was no significant difference between the scalp and non scalp shaven groups as regards to their age of presentation, sex, birth weight, GA at birth, mode and place of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…9 Using a rule requiring observation of at least 1 of 9 clinical signs of sepsis and other severe illness, the authors found a diagnostic performance of clinical assessment of 0.83 sensitivity and 0.62 specificity. For the hypothetical POCT for sepsis we assumed the same sensitivity as clinical assessment to ensure parity in survival.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 However, the detection of bloodstream infections presents a number of challenges. Clinical assessment using algorithms such as the World Health Organization (WHO) Integrated Management of Childhood Illness (IMCI) and WHO Integrated Management of Adolescent and Adult Illness (IMAI) can be rapid but lack sensitivity and specificity, 9 which risks overtreatment of patients without sepsis and failure to treat others. Blood cultures are considered the reference standard laboratory tests for the detection of bloodstream infections, but these lack sensitivity and do not produce results in a timeframe that can inform initial patient management.…”
Section: Introductionmentioning
confidence: 99%